SUITABILITY EVALUATION FOR OUTPATIENT THE PRESCRIPTION DRUG FORMULARY IN ONE PROVIDER HEALTH INSURANCE COMMERCIAL IN BANDUNG - Kusumahati, Eva
Background : the use of drug formulary in insurance system can ensure a quality standard prescription and cost efficiency. However, many prescribers prescribe non-formulary drugs that cause inconvenience among the insurance participants. This study was aimed to identify and assess the compliance of prescriptions to an insurance formulary. Methods : This was an observational and descriptive study on prescriptions received at depot of a private hospital in Bandung, prescribed to participants of a commercial insurance company. Quantitative analyses to evaluate prescriber’s prescription were carried out based on several criteria, including the polyclinic of origin, generic or non-generic and the suitability of diagnosis with therapeutic class listed in the formulary. Qualitative analyses assessed the prescription drugs which were filled. The information collected would demonstrate the compliance of prescription to the formulary. Results : Prescription containing nonformulary drugs were found in 15 out of 25 polyclinics in the depot. Meanwhile, 363 (42%) generic and 535 (58%) non-generic items were prescribed. Based on sub-therapeutic class derived from 330 prescriptions, there were 27 (8%) prescriptions containing non-formulary drugs, while those of formulary drugs were 303 (92%) prescriptions. Review on the suitability of prescription with diagnosis showed 100 % of conformity. Conclusion : Quantitative analyses showed that 8% out of 898 drug items did not belong to the formulary, while qualitative analyses revealed that some prescribers prescribed nonformulary drugs.